THE TREND OF STUDIES RELATED TO MYASTHENIA GRAVIS AND GENETICS IN VARIOUS POPULATIONS AROUND THE WORLD - Fitri, Dwiki; Irham, Lalu Muhammad; Sulistyani, Nanik; Adikusuma, Wirawan; Sianu, Rahman S; Ma’ruf, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
Myasthenia gravis (MG) is an autoimmune disease involving the neuromuscular junction, mainly influenced by antibodies to acetylcholine receptors. In addition, antibodies to Muscle-Specific Kinase (MUSK), Low-Density Lipoprotein Receptor-Related Protein 4 (LRP4). It is essential to determine publication trends regarding Myasthenia gravis because, currently, there are no studies that describe Myasthenia gravis publication trends related to genes in this field of study. Bibliometric analysis is used to see research trends, including frequently used keywords, most published journals, most cited publishers, author agencies, and collaboration between authors depicted in visualization using the VOSViewer application. Bibliometric analysis shows that the research trend is increasing from 1969 to 2023. The most frequently used keywords are myasthenia gravis, human, autoimmune disease, genetics, and article. The leading information related to the data is that the average annual publication is 5.89%, and the average citation for documents is 13.9%. Indonesia, as one of the countries experiencing Myasthenia gravis, has excellent potential to increase the number of research articles, which can be a means of exchanging knowledge, ideas, and technology and also has the potential for collaboration with other countries